DETERMINANTS OF CERVICAL CANCER SCREENING PRACTICES AMONG HIV INFECTED AND UNINFECTED WOMEN ATTENDING BINGHAM UNIVERSITY TEACHING HOSPITAL IN JOS, PLATEAU STATE, NIGERIA: COMPARATIVE STUDY. - Kefas, Ibrahim Bakshak; Isiko, Isaac; Okoro, Lenz Nwachinemere; Isa, Haroun; Bulus, Naya Gadzama; Asingwire, Jackson Micheal; Richman, Fortune Sunday; Kefas, Ibrahim Jane; Dogo, Joy Malle (Student's Journal of Health Research Africa, 2024)
Purpose This study focused on identifying the determinants of cervical cancer screening practices among HIV-infected and uninfected women attending Bingham University Teaching Hospital in Jos, Plateau State of Nigeria. Methods This was a comparative cross-sectional study that included women aged 15 to 49 years who had given birth at least once in their lifetime, both HIV-infected and uninfected, who attended Bingham University Teaching Hospital, Jos, Nigeria. Structured questionnaires were used to collect the data, and the collected data were cleaned and analyzed using the Statistical Package for Social Sciences (SPSS) software. Results There were significantly more HIV-infected women aged 35-44 years (AOR 5.71, CI 1.27-25.62, p = 0.023), the determinants from the study were employment status- employed uninfected women (AOR 5.11, CI 1.60-16.29, p = 0.006) and ethnicity- non-Plateau ethnicity uninfected women (AOR 7.44, CI 1.67-33.05, p = 0.007) with cervical cancer screening practices. None of the other determinants were significantly related to cervical cancer screening practices. Conclusion There was a low level of screening in both groups which means there is a need to increase cervical cancer awareness among both HIV-infected and uninfected populations.